2021
DOI: 10.1002/bies.202100148
|View full text |Cite
|
Sign up to set email alerts
|

Degeneracy in the nervous system: from neuronal excitability to neural coding

Abstract: Degeneracy is ubiquitous across biological systems where structurally different elements can yield a similar outcome. Degeneracy is of particular interest in neuroscience too. On the one hand, degeneracy confers robustness to the nervous system and facilitates evolvability: Different elements provide a backup plan for the system in response to any perturbation or disturbance. On the other, a difficulty in the treatment of some neurological disorders such as chronic pain is explained in light of different eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 159 publications
1
27
0
Order By: Relevance
“…In fact, to repair a failed degenerate system, it is often not enough to restore a single target mechanism (Figure 4). One reason for this is that, due to degeneracy, many different pathologically altered mechanisms are sufficient, but usually none of them is by itself necessary for pathological malfunction (Kamaleddin, 2022). In addition, a degenerate nervous system sometimes displays compensatory adaptations, which undermine therapeutic interventions focusing on a single target (Ratté et al, 2014;Ratté and Prescott, 2016).…”
Section: Similar Lfp and Eeg Discharges Despite Diversity Of Underlyi...mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, to repair a failed degenerate system, it is often not enough to restore a single target mechanism (Figure 4). One reason for this is that, due to degeneracy, many different pathologically altered mechanisms are sufficient, but usually none of them is by itself necessary for pathological malfunction (Kamaleddin, 2022). In addition, a degenerate nervous system sometimes displays compensatory adaptations, which undermine therapeutic interventions focusing on a single target (Ratté et al, 2014;Ratté and Prescott, 2016).…”
Section: Similar Lfp and Eeg Discharges Despite Diversity Of Underlyi...mentioning
confidence: 99%
“…Degeneracy, "the ability of elements that are structurally different to perform the same function or yield the same output" (Edelman and Gally, 2001), is a general principle, present in most complex adaptive biological systems (Tononi et al, 1999;Edelman and Gally, 2001). Degeneracy should be distinguished from redundancy, which results from multiple identical elements performing the same function (Edelman and Gally, 2001;Mason et al, 2015;Man et al, 2016;Kamaleddin, 2022; but see also Mizusaki and O'Donnell, 2021). In contrast to redundant components, degenerate components may generate dissimilar outputs in different contexts (Tononi et al, 1999;Morozova et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degeneracy [7] is present at all scales of the brain (figure 1). Its importance for the flexibility and robustness of brain functions has been increasingly acknowledged in recent years (for reviews see [9][10][11]). Accordingly, ion channel degeneracy has been linked to the flexibility [4] and robustness of neuronal behaviour [10,12,13].…”
Section: Ion Channel Degeneracy In Population Models Of Neuronsmentioning
confidence: 99%
“…Second, in line with a multi-causal pathogenesis, we showed that the increased excitability of CA1 pyramidal cells can be sufficiently accounted for by a shift in E/I balance towards glutamatergic network excitation (increased network burst activity and decreased inhibitory inputs) or by its combination with changes in ion channel expression ( I AHP channel density down-regulated; I Nap , I Na and I CaT up-regulated). Our results are in line with the concept of degeneracy (Tononi et al ., 1999; Edelman and Gally, 2001), according to which similar physiological but also similar pathological states such as neural hyperexcitability can emerge from multiple structurally distinct mechanisms (Neymotin et al ., 2016; Ratté and Prescott, 2016; O’Leary, 2018; Kamaleddin, 2022; Medlock et al ., 2022; Stö ber et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%